Getting it right, a training course for organizers and implementers of multi-stakeholder forums - Evans, K.; Monterroso, I. (Center for International Forestry Research, 2021)
This Training Course is tailored to support multi-stakeholder forums (MSFs) that focus on a range of environmental and development issues including forest management, protected area management, forest landscape restoration, sustainable agriculture, climate change, carbon mitigation and financing mechanisms. It is designed to provide facilitators with the materials needed to run a four-hour training course on how to address inclusion in MSFs. This training course goes hand-in-hand with the recent Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) publication Getting it right: A guide to improve inclusion in multi-stakeholder forums.